Internal control in teaching performance and its relationship with the achievement of institutional objectives. Case: Universidad Técnica de Manabí - Salazar Cobeña, Gladys Varinia (2019)
Objective: This research aimed to determine internal control in teaching performance and its relationship with the achievement of the institutional objectives of the Universidad Técnica de Manabí. Method: The focus of the study is quantitative, the type was a descriptive, correlational and exploratory research, with a non-experimental cross-sectional design. A Likert scale questionnaire with a Cronbach Alpha reliability coefficient of 0.81 was applied to 216 teachers of the faculties and institutes that teach subjects to all the University degree courses. The results of the comprehensive evaluation of the teaching performance of the 2017-2018 period generated by the Academic Management System were compiled and the performance levels were categorized according to the Regulation of Integral Evaluation of the Academic Personnel Performance of the Technical University of Manabí of 2017. Results: The results revealed that the majority of the evaluations were in the highest category and that there is a direct statistical correlation between the level of performance of the teaching human talent and the achievement of institutional objectives. Conclusions: It is concluded that the level of internal control in teacher performance does not contribute to the achievement of institutional objectives, as a result of the university not having a formal internal control system to supervise the fulfillment of the substantive functions of higher education.